2021
DOI: 10.1111/jace.17652
|View full text |Cite
|
Sign up to set email alerts
|

Formation of liquid‐phase isolation layer on the corroded interface of MgO/Al2O3‐SiC‐C refractory and molten steel: Role of SiC

Abstract: Formation of a dense layer on corroded interface to suppress corrosion is always desired, but it is controlled by numerous environmental conditions. In this work, corroded microstructures of MgO/Al2O3‐SiC‐C refractories in metal bath area of ladle furnace were investigated after industrial trails. A liquid‐phase isolation layer in which MgO islands and liquid phases was established on the corroded interface of refractories with 6 wt% coarse/fine SiC‐additive. The formed isolation layer against steel/slag attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…However, because the formation conditions of the MgO dense layer are very harsh and are affected by many factors, the accuracy of the theory remains to be verified 31 . In addition, studies have shown that the introduction of some additives can effectively prevent the penetration of the slag into the refractories by forming a high‐viscosity liquid phase isolation layer at the slag‐refractory interface 32 . This theory is consistent with the corrosion test results of this work.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…However, because the formation conditions of the MgO dense layer are very harsh and are affected by many factors, the accuracy of the theory remains to be verified 31 . In addition, studies have shown that the introduction of some additives can effectively prevent the penetration of the slag into the refractories by forming a high‐viscosity liquid phase isolation layer at the slag‐refractory interface 32 . This theory is consistent with the corrosion test results of this work.…”
Section: Resultssupporting
confidence: 79%
“…31 In addition, studies have shown that the introduction of some additives can effectively prevent the penetration of the slag into the refractories by forming a high-viscosity liquid phase isolation layer at the slag-refractory interface. 32 This theory is consistent with the corrosion test results of this work. First of all, samples M0 and M7.5 present greater corroded depth due to high apparent porosity (9.05% and 8.92%, respectively); secondly, samples M2.5, M5, and M7.5 all show a small penetrated depth due to the formation of a high-viscosity isolation layer (the role of Si provided by composite powder); thirdly, the in situ spinel formed between Al 2 O 3 in the composite powder and MgO also contributes to the improvement of the slag resistance of the MgO-C samples.…”
Section: Effects Of As-synthesized Al 2 O 3 -Sic Powder On the Oxidat...supporting
confidence: 92%
“…To assist in clarification of the mechanisms underpinning the whole reaction/synthesis process, thermodynamic calculations were carried out using the commercial FactSage package [40]. The Gibbs energy values for each of the intermediate reactions and the overall reaction (Reaction (1)), as a function of temperature, were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…
Incorporation of magnesia alumina spinel confers excellent thermal shock/spalling resistance, good slag resistance, high creep resistance and refractoriness, on calcium aluminate cement bonded corundum-magnesia alumina spinel (Al 2 O 3 -MgAl 2 O 4 ) refractory castables. [1][2][3][4] To date, they have been widely applied as lining materials in refining ladles, 1,5,6 Ruhrstahl Heraeus (RH) snorkels, 7-9 purging plug, 10 and slagging gasifiers, 11-12 etc.Their corrosion behaviors in the clean steel refining processes mentioned above have been extensively investigated. [13][14][15][16][17] Zhang and Lee studied the dissolution processes of fused and tabular corundum aggregates in a silicate slag, and observed the formation of calcium hexaaluminate (CA 6 ) and hercynitic spinel layers close to the Al 2 O 3 /slag interfaces, whose continuity and morphology varied, dominating the indirect or direct dissolution processes.
…”
mentioning
confidence: 99%
“…Incorporation of magnesia alumina spinel confers excellent thermal shock/spalling resistance, good slag resistance, high creep resistance and refractoriness, on calcium aluminate cement bonded corundum-magnesia alumina spinel (Al 2 O 3 -MgAl 2 O 4 ) refractory castables. [1][2][3][4] To date, they have been widely applied as lining materials in refining ladles, 1,5,6 Ruhrstahl Heraeus (RH) snorkels, 7-9 purging plug, 10 and slagging gasifiers, 11-12 etc.…”
mentioning
confidence: 99%